Methylprednisolone versus intravenous immunoglobulins in children with paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS): an open-label, multicentre, randomised trial. (April 2023) - Welzel, Tatjana; Atkinson, Andrew; Schöbi, Nina; Andre, Maya C; Bailey, Douggl G N; Blanchard-Rohner, Geraldine; Buettcher, Michael; Grazioli, Serge; Koehler, Henrik; Perez, Marie-Helene; Trück, Johannes; Vanoni, Federica; et al.
Summary: Background: The emergence of paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS) led to the widespread use of anti-inflammatory treatments in the absence of evidence from randomised controlled trials (RCTs). We aimed to assess the effectiveness of intravenous methylprednisolone compared with intravenous immunoglobulins. Methods: This is an open-label, multicentre, two-arm RCT done at ten hospitals in Switzerland in children younger than 18 years hospitalised with PIMS-TS (defined as age <18 years; fever and biochemical evidence of inflammation, and single or multiorgan dysfunction; microbiologically proven or putative contact with SARS-CoV-2; and exclusion of any other probable disease). Patients were randomly assigned 1:1 to intravenous methylprednisolone (10 mg/kg per day for 3 days) or intravenous immunoglobulins (2 g/kg as a single dose). The primary outcome was length of hospital stay censored at day 28, death, or discharge. Secondary outcomes included proportion and duration of organ support. Analyses were done by intention-to-treat. The study was registered with Swiss National Clinical Trials Portal (SNCTP000004720) and ClinicalTrials.gov (NCT04826588 ). Findings: Between May 21, 2021, and April 15, 2022, 75 patients with a median age of 9·1 years (IQR 6·2–12·2) were included in the intention-to-treat population (37 in the methylprednisolone group and 38 in the intravenous immunoglobulins group). The median length of hospital stay was 6·0 days (IQR 4·0–8·0) in the methylprednisolone group and 6·0 days (IQR 5·0–8·8) in the intravenous immunoglobulins group (estimated effect size –0·037 of the log10 transformed times, 95% CI –0·13 to 0·065, p=0·42). Fewer patients in the methylprednisolone group (ten [27%] of 37) required respiratory support compared with the intravenous immunoglobulin group (21 [55%] of 38, p=0·025). Need and duration of inotropes, admission to intensive care units, cardiac events after baseline, and major bleeding and thrombotic events were not significantly different between the study groups. Interpretation: In this RCT, treatment with methylprednisolone in children with PIMS-TS did not significantly affect the length of hospital stay compared with intravenous immunoglobulins. Intravenous methylprednisolone could be an acceptable first-line treatment in children with PIMS-TS. Funding: NOMIS Foundation, Vontobel Foundation, and Gaydoul Foundation.